2005
DOI: 10.1038/sj.ijo.0802883
|View full text |Cite
|
Sign up to set email alerts
|

Association of adipose tissue deposition and beta-2 adrenergic receptor variants: the IRAS family study

Abstract: OBJECTIVE: Adipose tissue distribution (visceral vs subcutaneous) has been shown to be an important predictor of insulin resistance, diabetes and cardiovascular disease, independent of body mass index. The beta-2 adrenergic receptor is a major lipolytic receptor in human fat cells and the gene that codes for this protein is an important candidate gene for measures of adiposity and fat deposition. We examined whether two common polymorphisms in codons 16 (Arg16Gly) and 27 (Gln27Glu) are associated with measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 49 publications
3
34
0
4
Order By: Relevance
“…Several studies, in agreement with our results, did not find association between the Gln27Glu polymorphism of the ADRB2 gene and obesity or related parameters (Bea et al 2010;Echwald et al 1998;Kortner et al 1999). Most positive findings with the Gln27Glu polymorphism suggest that the favorable allele is the Gln27 allele, and the Glu27 allele contributes to obesity risk (Clement et al 1995;Gonzalez Sanchez et al 2003;Lange et al 2005;Large et al 1997). Contrary, other researchers showed that the Gln27 allele enhances the risk of obesity (Meirhaeghe et al 2000;Pereira et al 2003).…”
Section: Baseline -Gln27glu and Trp64arg Polymorphismssupporting
confidence: 77%
See 1 more Smart Citation
“…Several studies, in agreement with our results, did not find association between the Gln27Glu polymorphism of the ADRB2 gene and obesity or related parameters (Bea et al 2010;Echwald et al 1998;Kortner et al 1999). Most positive findings with the Gln27Glu polymorphism suggest that the favorable allele is the Gln27 allele, and the Glu27 allele contributes to obesity risk (Clement et al 1995;Gonzalez Sanchez et al 2003;Lange et al 2005;Large et al 1997). Contrary, other researchers showed that the Gln27 allele enhances the risk of obesity (Meirhaeghe et al 2000;Pereira et al 2003).…”
Section: Baseline -Gln27glu and Trp64arg Polymorphismssupporting
confidence: 77%
“…While some researchers found that the Glu27 is the risk allele for obesity (Clement et al 1995;Gonzalez Sanchez et al 2003;Lange et al 2005;Large et al 1997), on the contrary others reported that the Glu27 is the favorable allele, protective against obesity (Meirhaeghe et al 2000;Pereira et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Second, we investigated ten polymorphisms in nine genes (ADRB1, ADRB2, ADRB3, CAPN10, IRS1, UCP2, PPARGC1A, PTPN1 and ENPP1), each of which has been associated with at least two components contributing to the metabolic syndrome [19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…nos ratos do grupo H, uma vez que o acúmulo de gordura na região abdominal tem sido relatado como fator determinante no desenvolvimento da resistência à insulina, e por ser este tecido metabolicamente mais ativo do que o tecido adiposo periférico 21,22 . O aumento do peso relativo do TAM nos ratos alimentados com a dieta hiperlipídica (Tabela 1), comparado aos controles, é concordante com outros estudos da literatura 19,23,24 .…”
Section: Figura 1 Evolução Do Peso Corporal Dos Ratos (G) Variaçãounclassified